The Influence of The Medical Service Sharing System and Work Motivation on Employee Performance at RSUD Dr. Tc Hillers - Defranky Theodorus; Laura Lahindah (Green Publisher Indonesia, 2025)
This study aims to analyze the effect of medical service sharing system and work motivation on employee performance at RSUD dr. TC Hillers Maumere. Data was collected from 265 hospital employees using questionnaires. Data analysis was conducted by using multiple linear regression SPSS version 26 Windows. The results showed that the medical service sharing system has a positive and significant influence on employee performance with an unstandardized coefficient beta of 0.433 and a t value of 9.776 (p 0.000). Work motivation also has a positive and significant influence on employee performance with an unstandardized coefficient beta of 0.163 and a t value of 4.468 (p < 0.000). This study supports Herzberg's Two-Factor Theory and Deci and Ryan's Self-Determination Theory, which emphasize the importance of intrinsic motivation and hygiene factors in improving employee performance. The managerial implication of this study is the importance of a fair medical services sharing system and work motivation enhancement programs to improve employee performance.